2001
DOI: 10.2337/diacare.24.5.933
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal Muscle Triglyceride

Abstract: Recent evidence derived from four independent methods indicates that an excess triglyceride storage within skeletal muscle is linked to insulin resistance. Potential mechanisms for this association include apparent defects in fatty acid metabolism that are centered at the mitochondria in obesity and in type 2 diabetes. Specifically, defects in the pathways for fatty acid oxidation during postabsorptive conditions are prominent, leading to diminished use of fatty acids and increased esterification and storage o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
253
1
5

Year Published

2001
2001
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 402 publications
(270 citation statements)
references
References 108 publications
11
253
1
5
Order By: Relevance
“…Since the present study included an endurancetrained group, this is consistent with data from Goodpaster and colleagues [31], and is in line with previous studies that did not find coupling when muscle triacylglycerol was measured biochemically in samples of muscle tissue [3,32]. It is generally thought that excess intramyocellular lipid storage results in decreased insulin sensitivity because an increased fatty acid precursor supply leads to increased concentrations of one or more of the lipid intermediates: diacylglycerol, long-chain fatty acyl-CoA or ceramide [9,33,34]. In support of this notion, Itani and colleagues found that insulin sensitivity was decreased after increasing plasma NEFA with a lipid infusion during an euglycaemic-hyperinsulinaemic clamp, and this occurred in parallel with an increase in intramuscular diacylglycerol, but not ceramide [15].…”
Section: Basalsupporting
confidence: 92%
“…Since the present study included an endurancetrained group, this is consistent with data from Goodpaster and colleagues [31], and is in line with previous studies that did not find coupling when muscle triacylglycerol was measured biochemically in samples of muscle tissue [3,32]. It is generally thought that excess intramyocellular lipid storage results in decreased insulin sensitivity because an increased fatty acid precursor supply leads to increased concentrations of one or more of the lipid intermediates: diacylglycerol, long-chain fatty acyl-CoA or ceramide [9,33,34]. In support of this notion, Itani and colleagues found that insulin sensitivity was decreased after increasing plasma NEFA with a lipid infusion during an euglycaemic-hyperinsulinaemic clamp, and this occurred in parallel with an increase in intramuscular diacylglycerol, but not ceramide [15].…”
Section: Basalsupporting
confidence: 92%
“…The evaluation of different fat compartments in the human body is extremely important since regional fat depots and health risks are correlated (125)(126)(127). Many different methods such as MRI/MRSI, computed tomography (CT) and dual-energy X-ray absorptiometry (DXA) are used to evaluate body composition and in particular the regional distribution of fat (125)(126)(127)(128)(129).…”
Section: Mri Of Muscular Fat and Estimation Of Other Lipid Compartmenmentioning
confidence: 99%
“…Many different methods such as MRI/MRSI, computed tomography (CT) and dual-energy X-ray absorptiometry (DXA) are used to evaluate body composition and in particular the regional distribution of fat (125)(126)(127)(128)(129). While many studies have been published that were instrumental in improving understanding of lipid metabolism in general, a review of these publications would be beyond the limits of this article, which focuses on the observation of muscular lipids by means of 1 H-MRS.…”
Section: Mri Of Muscular Fat and Estimation Of Other Lipid Compartmenmentioning
confidence: 99%
“…Reduced plasma fatty acid uptake and oxidation by the leg [7] and the arm [8,9] have been observed in type 2 diabetics as compared to healthy individuals. Moreover, the relationship between intramuscular lipid accumulation and insulin resistance has been described [10,11]. Physical inactivity or muscle disuse is recognised as one of the risk factors for the development of insulin resistance and type 2 diabetes [12,13].…”
Section: Introductionmentioning
confidence: 99%